2013
DOI: 10.1021/am400442z
|View full text |Cite
|
Sign up to set email alerts
|

Effective Solubilization of Single-Walled Carbon Nanotubes in THF Using PEGylated Corannulene Dispersant

Abstract: PEG-derivatized corannulene compound has been found to be very effective in solubilizing single-walled carbon nanotubes in tetrahydrofuran. Solubilizing efficiency is close to the commonly used anionic surfactant, sodium dodecyl sulfate (SDS). Corannulene derivative has also been found to have a tendency to disperse metallic nanotubes more effectively than the SDS counterpart. Theoretical calculations predict higher dispersion interactions of corannulene backbone with the convex surface of nanotubes in compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…We focused here on the ratio of Gband intensity to G + band intensity (I G-/I G+ ). Since I G-/I G+ value indicates the degree of metallic SWNTs existence, some studies which discuss the selectivity of dispersant to specific SWNTs has been reported [8]. Meanwhile, the ratio of D band intensity to G band intensity (I D /I G ) value is helpful to determine the degree of impurity such as defect of SWNTs and amorphous carbon [29].…”
Section: Analyses Of Precipitates By Ft-ir Spectra and Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…We focused here on the ratio of Gband intensity to G + band intensity (I G-/I G+ ). Since I G-/I G+ value indicates the degree of metallic SWNTs existence, some studies which discuss the selectivity of dispersant to specific SWNTs has been reported [8]. Meanwhile, the ratio of D band intensity to G band intensity (I D /I G ) value is helpful to determine the degree of impurity such as defect of SWNTs and amorphous carbon [29].…”
Section: Analyses Of Precipitates By Ft-ir Spectra and Raman Spectramentioning
confidence: 99%
“…This represents a significant obstacle to purify carbon nanotubes and fabricate carbon nanotube devices, and the techniques for individually dispersing carbon nanotubes have being actively researched. For example, the individual dispersion of single-walled carbon nanotubes (SWNTs) without molecular modification can be achieved by adsorption of surfactants [2][3][4][5][6] or ionic liquid surfactants [7] in aqueous or organic solvents [8]. Block co-polymers [9] and DNA [10] can also produce the individual dispersion of SWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Corannulene decorated by polyethylene glycol (PEG) (PEGylated corannulene) was found to be a very effective dispersant for single‐wall carbon nanotubes (SWCNTs) in THF . The efficiency of PEGylated corannulene for SWCNTs is close to the commonly used anionic surfactant, sodium dodecyl sulfate (SDS).…”
Section: Derivatives Of Corannulenementioning
confidence: 99%
“…The MM3 force-eld is known for reasonable predictions of the sp 2 -hybridized structures of many conjugated molecules. 33 However, MM3 lacks adequate parameters to model the pyrrole rings in the carbazole oligomers. To solve this, MM3-2000 force-eld parameters 34,35 have been modied to reproduce the geometries of the isolated carbazole oligomers obtained from Density Functional Theory (DFT) calculations using the B3LYP functional with the 6-31G(d) basis set, as implemented in the GAUSSIAN-09 soware package.…”
Section: Computational Detailsmentioning
confidence: 99%